2021
DOI: 10.1017/jfm.2021.84
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities and transition in cooled wall hypersonic boundary layers

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Laurence et al (2016) experimentally demonstrated a similar kink in the development of a wave packet in a high-enthalpy boundary layer and attributed it to nonlinear effects. Unnikrishnan & Gaitonde (2021) showed that wave packets in highly cooled boundary layers become increasingly nonlinear as they elongate, unlike warmer-wall cases where packets split into a clear nonlinear head and a separate, linear trailing region. Thus, the observations made for this burst of content could be attributed to acoustic radiation, nonlinear interactions or a combination of the two.…”
Section: Bandpass Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Laurence et al (2016) experimentally demonstrated a similar kink in the development of a wave packet in a high-enthalpy boundary layer and attributed it to nonlinear effects. Unnikrishnan & Gaitonde (2021) showed that wave packets in highly cooled boundary layers become increasingly nonlinear as they elongate, unlike warmer-wall cases where packets split into a clear nonlinear head and a separate, linear trailing region. Thus, the observations made for this burst of content could be attributed to acoustic radiation, nonlinear interactions or a combination of the two.…”
Section: Bandpass Filteringmentioning
confidence: 99%
“…For example, Chuvakhov & Fedorov (2016) suggested that the mechanism may delay the transition to turbulence. Unnikrishnan & Gaitonde (2020, 2021) addressed this postulate, maintaining that the destabilization of perturbations within the boundary layer would have a stronger effect promoting transition than the radiated energy would have in delaying it. Finally, nose bluntness has also been shown to have a significant effect on the supersonic mode, with the LST and DNS of Mortensen (2018) demonstrating a strong coupling between increased nose radius (up to a certain point) and instability growth rate; effects of oxygen dissociation were also observed to have a significant effect.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the TWPs and the Mack modes in hypersonic turbulent boundary layer transition share many similar features. For example, (i) they share the same morphology, behaving as the travelling waves with a certain wavenumber, (ii) they are both located close to the wall, (iii) the TWPs are intensified by the rising Mach number and the cooling wall (Yu et al 2019;Unnikrishnan & Gaitonde 2021;Yu & Xu 2021), and the second mode is destabilized by these factors (Mack 1984;Stetson & Kimmel 1992), and (iv) they can both enhance the wall pressure fluctuations (Casper, Beresh & Schneider 2014;Yu et al 2020;Unnikrishnan & Gaitonde 2021). It is probably the different base flows that lead to the disparity in the growth of these perturbations.…”
Section: Transient Growth On a Steady Streakmentioning
confidence: 99%
“…2019; Unnikrishnan & Gaitonde 2021; Yu & Xu 2021), and the second mode is destabilized by these factors (Mack 1984; Stetson & Kimmel 1992), and (iv) they can both enhance the wall pressure fluctuations (Casper, Beresh & Schneider 2014; Yu et al. 2020; Unnikrishnan & Gaitonde 2021). It is probably the different base flows that lead to the disparity in the growth of these perturbations.…”
Section: Numerical Experiments and Flow Dynamicsmentioning
confidence: 99%
“…Over the insulated wall, the developed boundary layer is thicker, approximately δ h0 ≃ 14 mm, in contrast to δ h0 ≃ 8 mm over the cold wall. Unnikrishnan et al [43] noted that second-mode instabilities tend to exhibit maximum amplitudes near highgradient regions. Consequently, amplification dynamics are intensified closer to the wall under colder surface conditions.…”
Section: Steady Statementioning
confidence: 99%